Peranan Sektor Transportasi dan Pengeluaran Pemerintah Dalam Pertumbuhan Ekonomi Indonesia: Analisis Input-Output - Miftahul Fauziyah; Doni Satria (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study analyzes the role of the transportation sector and government spending on Indonesia's economic growth, as measured by input-output analysis. The method used is input-output analysis, which measures the backward and forward linkages in the transportation sector and the multiplier effect on output, income, and employment in the Indonesian economic sector. This study uses input-output data from 185 sectors in 2020, with the transportation sector aggregated to 179 sectors in total, processed using Microsoft Excel. The analysis shows that the transportation sector has the ability to push and pull within the transportation sector itself. Meanwhile, the distribution power index indicates that the transportation sector is less attractive than other sectors, while the sensitivity of the transportation sector is able to drive sector output growth in Indonesia.